Pemaknaan dan Nilai dalam Upacara Adat Maras Taun di Kabupaten Belitung - Asep Dadan Wildan; Moh. Dulkiah; Irwandi Irwandi (PANGGUNG, 2019)
ABSTRACT This paper aims to find out the meaning and values of the tradition of the Maras Taun ceremony in Belitung Regency. This research is conducted using a qualitative method with sociology and cultural anthropology approaches. Maras Taun is one of the traditional ceremonies that has been carried out for generations in Belitung Regency. It is not just a routine activity in Belitung Island, but at least there are three dimensions contained in the ceremony including tradition, symbolism, and values. Maras Taun is a thanksgiving ceremony for rice harvest which is carried out once a year after the harvest because most of the people earn a living in the fields. The next development of the Maras Taun ceremony is transformed into village salvation as people were not farmed in the fields anymore because of social changes. But, this did not reduce the sacredness of the traditional ceremony of Maras Taun itself. The results of this study found that in each stage of the ceremony contained the symbols and values of cultural practices of the community.Keywords: Tradition of Maras Taun, meaning and values, Belitung RegencyABSTRAK Tulisan ini bertujuan untuk mengetahui makna dan nilai tradisi upacara adat Maras Taun di Kabupaten Belitung. Penelitian ini dilakukan dengan menggunakan metode kualitatif dengan pendekatan sosiologi dan antropologi budaya. Maras Taun merupakan salah satu upacara adat yang dilaksanakan secara turun-temurun oleh masyarakat di Kabupaten Belitung. Maras Taun tidak hanya sekadar sebuah perayaan rutin yang setiap tahun oleh setiap desa di Pulau Belitung, namun dalam perayaan tersebut setidaknya terdapat tiga dimensi, yakni tradisi, simbolisme, dan nilai. Maras Taun merupakan upacara syukuran panen padi yang dilaksanakan setahun sekali pasca panen padi, karena sebagian besar masyarakat bermata pencaharian petani ladang. Pada perkembangan selanjutnya. upacara ini bertransformasi menjadi selamatan kampung karena masyarakat sudah jarang yang bertani di ladang disebabkan adanya perubahan sosial. Namun hal tersebut tidak mengurangi kesakralan dari upacara adat tersebut. Hasil kajian ini menemukan bahwasanya setiap tahapan dalam upacara perayaan Maras Taun kaya akan simbol-simbol dan nilai yang terkandung di dalamnya.Kata Kunci: Tradisi Maras Taun, makna dan nilai, Kabupaten Belitung